2010
DOI: 10.1186/1741-7007-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic development of auditory sensitivity and sound production in the squeaker catfish Synodontis schoutedeni

Abstract: BackgroundSurveys of ontogenetic development of hearing and sound production in fish are scarce, and the ontogenetic development of acoustic communication has been investigated in only two fish species so far. Studies on the labyrinth fish Trichopsis vittata and the toadfish Halobatrachus didactylus show that the ability to detect conspecific sounds develops during growth. In otophysine fish, which are characterized by Weberian ossicles and improved hearing sensitivities, the ontogenetic development of sound c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 45 publications
6
52
0
Order By: Relevance
“…All species examined showed a broad range of sensitivity, as is known from other otophysan fishes [30][31][32][33].…”
Section: Discussionmentioning
confidence: 95%
“…All species examined showed a broad range of sensitivity, as is known from other otophysan fishes [30][31][32][33].…”
Section: Discussionmentioning
confidence: 95%
“…However, acoustic communication might be absent during early developmental stages because of poor hearing sensitivity, as in the gourami (Trichopsis vittata) (Wysocki and Ladich, 2001). Yet, at least in some species, it may occur during a wide range of developmental stages, as in the catfish (Synodontis schoutedeni) (Lechner et al, 2010). Nevertheless, these studies only focused on simple-pulsed sounds produced in distress/ agonistic contexts and they do not report any evidence of vocal differentiation that would facilitate acoustic communication in these species.…”
Section: Introductionmentioning
confidence: 99%
“…1 µPa at 0.8-3.0 kHz and a shift in the best frequency from 2.5 kHz to 1.5 kHz. Likewise, Lechner et al (2010Lechner et al ( , 2011 reported a considerable increase in auditory sensitivity and shift in the best frequency with development in two catfish species. Lechner et al (2010) reported an ontogenetic increase in Synodontis schoutedeni auditory sensitivity of 26 dB re.…”
Section: Ontogenetic Development Of Peripheral Auditory Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Blue catfish are also cannibalized by their own species (Chandler, 1998;Schloesser et al, 2011), and catfish have specialized hearing that is sensitive at low thresholds and high frequencies (Ladich, 1999;Ladich and Fay, 2013;Lechner et al, 2010;Papes and Ladich, 2011). Most fish predators that consume them would be less well tuned to the frequency spectrum of the blue catfish sounds than would bird predators (Dooling, 1982).…”
Section: Research Articlementioning
confidence: 99%